DILEMA DANT ANT ANGAN PEMBELAJARAN E-LEARNING - Hendrastomo, Grendi (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The main focus in this article is the learning model. One model that latelybecomes trend is the e-learning. Many strong points from e-learning areable to enhance the essence of learning. Students are pushed to seek formore knowledge, open the door of interaction between lecturers and themwidely, without any time nor place limitation. The strong pointsmentioned above are meant to maximize the process of learning whichhopefully will optimize the outcome.Dependency of e-learning with apparatus and technology on the otherhand, creates a dilemma and challenge all at once. Three key factorswhich need to be considered are human resources, supportinginfrastructures and implementation. In order to obtain an optimal resultof leami11g, these three factors have got to hold up to one and another.In point of fact, these three factors have not actually fuljilled due to 11w11yaspects; for instance, the quality of human resources whose not ye/ beenable to master e-learning, minimum infrastructure accessible and how todecide the most suitable learning .rnodel.